Calculus

posted by .

Implicit differentiation of 5x^2-2xy+7^y

• Calculus -

Two assumptions
1. you want dy/dx
2. You have the equation 5x^2 - 2xy + 7y^2 = 0

10x - 2x dy/dx - 2y + 14y dy/dx = 0
dy/dx( 14y - 2x) = 2y - 10x
dy/dx = (2y-10x)/(14y - 2x) = (y - 5x)/(7y - x)

• Calculus -

No, the equation is
5x^2-2xy+7^y

Last term has 7 to the y power....

• Calculus -

Ouch, nasty term ...

the derivative of 7^y would be
(ln7)(7^y)dy/dx

I am sure you can make the necessary changes .

• Calculus -

Yes...very nasty! Thanks

Similar Questions

1. Calculus 1 - implicit differentiation

I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
2. Calculus 1 - implicit differentiation

I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
3. Calculus 1 Implicit differentiation

Help please help me understand what i am doing wrong in this problem! x^3+3x^2y+y^3=8 find dy/dx using implict differentiation. The answer is x^2+2xy -------- but i keep getting x^2y x^2+y^2 ----- x^2+y^2
4. Calculus

Find dy/dx by implicit differentiation: x^2-2xy+y^3 = c Thank you!
5. Calculus

Use implicit differentiation to find the slope of the tangent line to the curve 2(x^2) + 2xy + 2(y^3)= -18
6. Calculus

I am having trouble differentiating x^2 + 2lny = y (solving for dy/dx). I know that I need to do implicit differentiation, but the answer I get is not correct. The answer I got was (2x-2xy)/2, but the answer is (2xy)/(y-2). How do …
7. Calculus

Find dy/dx by implicit differentiation. x^3 - 3x^2y + 2xy^2 =12 Please show me the work/steps on how to do it.
8. Calculus

Find dy/dx by implicit differentiation for x^2 - 2xy + y^3 = C
9. Calculus

Find dy/dx by implicit differentiation for x^2 - 2xy + y^3 = C
10. Calculus

Find y" by implicit differentiation. x^3+y^3 = 1 (x^3)'+(y^3)' = (1)' 3x^2+3y^2(y') = 0 3y^2(y') = -3x^2 y' = -3x^2/3y^2 y' = -x^2/y^2 y" = [(y^2)(-x^2)'-(-x^2)(y^2)']/y^4 y" = [(y^2)(-2x)-(-x^2)(2y)]/y^4 y" = [(-2xy^2)-(-2yx^2)]/y^4 …

More Similar Questions